Acute acalculous cholecystitis in a patient with juvenile dermatomyositis. (19th September 2014) - Sanches, Bruno Fernandes; Martins, Teresa; Santos, Maria José; Azeredo, Paula
Abstract : Juvenile dermatomyositis (JDM) is a rare autoimmune disease, characterised by a systemic capillary vasculopathy that typically affects skin and muscle. Gastrointestinal involvement is relatively rare. We report the case of an 11-year-old girl admitted for investigation of skin rash, progressive symmetric proximal muscle weakness, dysphagia and weight loss. The diagnosis of JDM was confirmed and during hospitalisation the patient developed abrupt and intense right hypocondrium pain associated with nausea and vomiting. Abdominal ultrasound revealed a thick gallbladder wall (8 mm) with pericholecystic fluid and no evidence of gallstones. An acute acalculous cholecystitis was assumed and the patient was started on intravenous fluids, prednisolone and analgaesic therapy. Clinical resolution was verified after 48 h. We hypothesised that the vasculitic process of JDM could have been the basis for this complication as described in other autoimmune diseases.